Zwischensprachliche Interferenz als Fehlerquelle in schriftlichen Arbeiten polnischer Germanistikstudenten - LIETZ, Gero (Wydawnictwo Naukowe UAM, 1996)
The article looks at error cause analysis with particular reference to errors due to negative transfer from the mother tongue. It describes an empirical study including 537 essays and Polish-German translations written by advanced learners of German at two Polish universities. Based on the statistical results of this study, main fields of Polish-German negative transfer are pointed out and discussed. The results show clearly that interference is not only a problem of beginners, but also of advanced learners at university level. About 25% of the total number of errors are caused by negative transfer (mainly from Polish, in some cases also from English as a third language). The interference rate in the translations, however, has proved to be somewhat higher than in the essays. The results of the error cause analysis described in this article show once again that the learners’ mother tongue should be taken into account in the process of foreign language teaching. Realizing the contrasts and the similarities between two languages can help to prevent negative transfer.